Working memory outcomes following unilateral arterial ischemic stroke in childhood. Issue 7 (3rd October 2017) - Fuentes, Amanda; Westmacott, Robyn; Deotto, Angela; deVeber, Gabrielle; Desrocher, Mary
ABSTRACT: There is a dearth of research examining working memory (WM) following pediatric arterial ischemic stroke (AIS). This study assesses the WM patterns of 32 children, aged 6 to 14 years, with a history of unilateral AIS and 32 controls using a paradigm based on Baddeley and Hitch's multi-component WM model. The results indicate compromised WM in children with AIS relative to controls and parent reports confirm higher rates of dysfunction. Supplementary analyses of impairment confirm higher rates in children with AIS, ranging from 31.25% to 38.70% on performance-based measures and 50.00% on parent reports, compared to 0.00% to 21.88% on performance-based measures in controls and 15.63% on parent reports. Continual follow-up is recommended given that a subset of children with stroke appear to be at risk for WM impairment. Moreover, the subtle nature of WM challenges experienced by many children who have experienced a stroke increases the likelihood that WM impairment could go undetected. The long-term trajectories of WM in the pediatric stroke population remains unknown and future studies are needed to track changes in WM functioning over time.